Low-impact development measure planning method based on multi-objective optimization and comprehensive evaluation - LIU QIMING; TAN QIAN; MENG XU; YAO LINLIN (2025)
The invention discloses a low-impact development measure planning method based on multi-objective optimization and comprehensive evaluation. The method comprises the following steps: collecting related data of a target area; constructing a rainstorm management model; determining an objective function, a decision variable and a constraint condition, and constructing a multi-objective optimization model based on a second-generation non-dominated sorting genetic algorithm; coupling the rainstorm management model with the multi-objective optimization model to obtain a coupling model, and performing iterative optimization on the coupling model to obtain an optimal solution set; determining a multi-target weight through an entropy weight method and an analytic hierarchy process, and comprehensively evaluating the optimal solution set according to the multi-target weight through an approximate ideal solution sorting method to obtain a low-impact development measure planning scheme; the objective function is determin